Migration and Remittances, A case study of Ghanaian students in Iceland - Agnes Enyonam Ahama 1990- (2024)
This research focuses on the migration and remittance practices of Ghanaian students in Iceland. Issues regarding the migration from Ghana to Iceland were discussed including how they adapt to the Icelandic society upon arrival while looking at how they manage to support their family and friends back in Ghana through remittances. This research aimed to gain insights into the reasons Ghanaian students travel to Iceland and the various challenges these students face in the pursuit of seeking higher education in a high-income country like Iceland. Four interviews with Ghanaian students attending the University of Iceland formed the basis of this study, which used qualitative research methods. The research's theoretical framework addresses notions about international migration from the south to the north. The topic of migration from the South to the North, particularly from Africa to the European Union (EU), has taken center stage in discussions about world development. This thesis explores the relationship between remittances and migration by concentrating on Ghanaian students studying in Iceland. This study aims to further our understanding of the dynamics of the international student movement by looking at the experiences of Ghanaian students studying in Iceland. Education is a major factor in migration, particularly for young Africans seeking to pursue higher education, perceived higher educational levels in the OECD are a factor in this migrant trend. Findings show that students particularly struggle with the challenge of the proof of funds the Icelandic Immigration requests from students before granting student permits and while in Iceland, adjusting to the Icelandic weather, language barrier, and cultural differences, and navigating their academic and social life are included in the challenges they face. On the other hand, remitting to support families left behind. Participants express their opinions regarding how life in Ghana is different from Iceland's and the new hobbies they have adopted to enjoy their ...